Long‐term evaluation of pemphigus vulgaris: A retrospective consideration of 98 patients treated in an oral medicine unit in north‐west Italy. (28th March 2019) - Arduino, Paolo G.; Broccoletti, Roberto; Carbone, Mario; Gambino, Alessio; Sciannameo, Veronica; Conrotto, Davide; Cabras, Marco; Sciascia, Savino; Ricceri, Fulvio; Baldovino, Simone; Carrozzo, Marco
Abstract : Background: Despite the frequency of oral involvement, there are unexpectedly few studies of either on the oral manifestations of pemphigus or their long‐term management, and diagnostic delay in Dentistry is frequent. Methods: We have examined outcome of patients presenting with predominantly oral pemphigus vulgaris (PV). Ninety‐eight subjects were followed up for 85.12 months and treated with systemic steroids: 48 of them received adjunctive therapy with azathioprine, 16 with rituximab, 13 with mycophenolate mofetil, three with immunoglobulin and one with dapsone. Results: Clinical remission was achieved in 80 patients (84.21%); 39 of them were off therapy and 41 on therapy. Fifteen patients were not in remission, having been under systemic therapy for 72.16 months. Sixty‐nine patients developed detectable adverse effects. Two fatal outcomes were recorded. Each additional year of steroid therapy ensured 47% chance of developing 1 or 2 side effects, and 64% chance of developing more than 3 (ORs 1.47, CI 1.162‐1.903; ORs 1.64, CI 1.107‐2.130, respectively). Conclusion: In one of the largest available cohort with the longest follow‐up ever reported, we observed that the management remains need‐based and patient‐specific, still relying on systemic corticosteroids.